1980
DOI: 10.1507/endocrj1954.27.supplement_141
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Immunoreactive Motilin

Abstract: Motilin-like immunoreactivities were examined in extracts of duodena of pig, human, dog, rat, cat, rabbit and guinea pig with a combination of radioimmunoassays using three different antisera possessing distinct region-specificities. Antisera GP-1103 and R-1104 were rather C-terminal specific, but the immunological feature of GP-1103 was different from that of R-1104. In the case of antiserum GP-1103, the Glu residue in position 15 in the motilin molecule participated in antigen-antibody interaction, but not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…3A). This might be in accordance with the observations by Yanaihara and his coworkers [9,10], who reported that the assay values for motilin depend on antisera with different specificity to epitopes in the motilin molecule.…”
Section: Discussionsupporting
confidence: 93%
“…3A). This might be in accordance with the observations by Yanaihara and his coworkers [9,10], who reported that the assay values for motilin depend on antisera with different specificity to epitopes in the motilin molecule.…”
Section: Discussionsupporting
confidence: 93%
“…Since the 22-amino-acid peptide (in the human and presumably other species) is encoded on two exons, motilin may in fact comprise two functional domains. Furthermore, the structure of the human motilin gene presented here may represent the basis for the interspecies heterogeneity in the motilin structure which has been observed or inferred by others (Shin et al, 1980). Thus, it is interesting to note that although there is complete amino acid identity between human and porcine motilin, 5 of 22 amino acids are different in canine motilin.…”
Section: Discussionsupporting
confidence: 64%
“…As compared to secretin, motilin required more stringent acidification of the mucosa to be released: the pH thresh old ranged from 1.0 to 1.9. This difference was not likely to reflect defective recognition of motilin-like components because this pep tide was measured with an assay based on the porcine peptide thus alleviating the potential problem of molecular heterogeneity as met with canine or human motilin [21,22], In addition, the immunoreactive substances de tected in plasma by the secretin and motilin assays were essentially similar to the stan dard preparations at gel chromatography.…”
Section: Discussionmentioning
confidence: 99%